Paolo VI: la santitta come „dramma di amore” - Cazzago, Aldino (Warszawskie Studia Teologiczne, 2019)
The article presents the teaching of Pope Paul VI on holiness. It shows the context of this teaching, which was the findings of the Second Vatican Council. The article shows how the pope understood what holiness is, how he understood the relationship between holiness and love, the role of the Church and the action of the Holy Spirit.